Shakespeare’s Richard III and Macbeth: A Foucauldian Reading - Ramin, Zohreh (k@ta: A Biannual Publication on the Study of Language and Literature, 2013)
Reading for signs of power and its function in the world of Shakespeare’s plays under the light of Michel Foucault reveals to be in stark contrast from traditional notions of the operation of power. An important Renaissance critic, E. M. Tillyard, has declared that Shakespeare’s plays reflect faithfully the Elizabethan world order, remaining loyal to the hierarchical concept of power and its function in Elizabethan England. Such readings engage mainly with the protagonist of the plays, revealing the various aspects in which the world of the play moves toward order and harmony. A Foucauldian reading of the plays however is able to unveil more than merely a one-dimensional reflection of power structures of the society of the time. By focusing on Foucault’s notion of power relations at work in the society and also his emphasis on the marginalized aspects, this study aims to reveal how power relations in the two plays under consideration, Richard III and Macbeth, can reveal versatile experiences.